Between inclusivity and feminist purism: Young gender justice workers in post-Nirbhaya Delhi. (March 2018) - Gilbertson, Amanda
Abstract: Gender justice is experiencing a moment of heightened visibility in India in the wake of the anti-rape protests of 2012/13. This paper seeks to understand this widening of the terrain of gender justice through an exploration of the work of young gender justice workers in Delhi. These young people practiced diverse politics and feminisms that challenge generational arguments of lost radicalism and linear conceptions of feminist history. Further, the messy hybridity of the feminisms and politics of individuals and organizations challenges neat conceptualizations of pure, authentic feminisms and co-opted, depoliticized feminisms. However, in the approach of some young people there is evidence of a distancing from the political and an individualizing and psychologizing of structural problems associated with choice, post and corporate feminisms. This transformation of gender justice into a matter of self-work points to potential risks of an overly inclusive feminism. Highlights: Young gender justice workers in Delhi express diverse politics and feminisms. This diversity suggests Indian feminism has not been entirely co-opted. Some young people depoliticize, individualize and psychologize gender justice work. They transform gender justice into a matter of self-work. Neoliberal feminisms beyond NGOization are relevant to analysis of the Global South.